Evaluasi Kinerja Fisik Sistem Subak Yang Berorientasi Agroekowisata Menggunakan Pendekatan Logika Fuzzy - S Sumiyati; Lilik Sutiarso; Wayan Windia; Putu Sudira (Jurnal Teknik Industri, 2011)
Along with the development of the tourism in Bali, one of the phenomena occurs was that the land conversion to the non-agricultural land, causing the canal irrigation was not able to function again. In addition, water demand will be increased not only for irrigation, but also for other sectors out of irrigation. This condition can interfere the performance of the subak system. One strategy to improve subak system is to develop agroecotourism based on subak system. Analysis of physical performance subak system done using fuzzy logic approach to quantify the condition of vagueness. Because of the problems associated with subak irrigation systemperformance are often vague and can not be classified with certainty. The results of this study are (i) the values of subak irrigation system performance indicators, the condition and thefunction of subak irrigation facilities, the condition and the function of subak facilities, and the agroecotourism facilities; (ii) find out the physical performance of subak irrigation systems in Bali with agroecotourism oriented. The stages of this research were collecting and analyting the data include: (i) RWS (Relative Water Supply), (ii) RIS (Relative Irrigation Supply),(iii) Ia (Index Area), (iv) analysis of the condition and function of subak irrigation networks, (v) the condition and the function of subak facilities, (vi) the agroecotourism facilities, and (vii) physical performance of subak system using fuzzy logic approach. The utilization rate of water on Subak Anggabaya and Subak Lodtunduh in one year was good. Subak Anggabayaand Subak Lodtunduh have sufficient irrigation water supply with RIS values in one year > 1. Based on Area Index (Ia), it could be seen that the irrigated area in Subak Anggabaya andSubak Lodtunduh in accordance with the plan. The physical performance of Anggabaya subak system and Lodtunduh Subak system was in the middle criteria. The simulation results that development of agroecotourism on subak system could improve the physical performance of subak system.